Organizational Factors, Adoption Issues and Value Creation of Digital Government - Dr Muhammad Habib; Dr. Sabir Ijaz; Dr.Fatima Agha Shah; Prof. Dr. Sajida Parveen; Dr. Zubaida Aziz; Shadab Akhtar (Al-Qanṭara, 2024)
In this modern era, there is an increasing need for digital government initiatives as global governments leverage technologies to improve the delivery of services to the citizens. Further, it comprises the increment in the efficiency of governance and nurtures all-inclusive societal growth. Nonetheless, the ultimate integration of the digital government initiatives is mainly obstructed by numerous adoption problems that involve the organisational, digital, technological and socio-economic factors. Therefore, this paper illustrates the major adoption issues in digital government issues, like security concerns, privacy of data and interoperability issues alongside the acceptance of the rapid change from conventional government to modern government. With the help of a detailed evaluation of these issues, the paper addresses the significance of these challenges to realise the overall effectiveness of digital transformation in the government landscape. Moreover, the creation of value to the digital government initiatives requires the improvements to the quality of services, innovation, efficiency gains, social inclusion and economic growth. The value creation is only possible with the mitigation of adoption issues and strategic implementation of data-driven decision-making and nurtures sustainable growth in this modern landscape of digital government.